Effect of Skull Type on the Relative Size of Cerebral Cortex and Lateral Ventricles in Dogs - Pilegaard, Anders M.; Berendt, Mette; Holst, Pernille; Møller, Arne; McEvoy, Fintan J. (Frontiers in Veterinary Science, 2017)
Volume measurements of the brain are of interest in the diagnosis of brain pathology. This is particularly so in the investigation hydrocephalus and canine cognitive dysfunction (CCD), both of which result in thinning of the cerebral cortex and enlarged ventricles. Volume assessment can be made using computed tomography or more usually magnetic resonance imaging (MRI). There is however some uncertainty in the interpretation of such volume data due to the great variation in skull size and shape seen in dog. In this retrospective study we examined normal MRI images from 63 dogs < 6 years of age. We used a continuous variable, the cranial index (CrI) to indicate skull shape and compared it to MRI volume measurements derived using Cavalieri's principle. We found a negative correlation between CrI and the ratio of cortical to ventricular volume. Breeds with a high CrI (large latero–lateral compared to rostro–caudal cranial cavity dimension) had a smaller ratio of cortical to ventricular volume (low C:V ratio) than breeds with lower CrI skull types. It is important to consider this effect of skull shape on the relative volume estimates of the cerebral cortex and ventricles when trying to establish if pathology is present.